Death of a policeman - Beaton, M. C. (Beaton, M. C. Hamish Macbeth mysteries, 2014)
"Local police stations all over the Scottish Highlands are being threatened with closure. This presents the perfect opportunity for Detective Chief Inspector Blair, who would love nothing more than to get rid of Sergeant Hamish Macbeth. Blair suggests that Cyril Sessions, a keen young police officer, visit the town of Lochdubh to monitor exactly what Macbeth does every day. Macbeth hears about Blair's plan and is prepared to insure that Cyril returns back to headquarters with a full report. But Cyril is soon found dead and Hamish quickly becomes the prime suspect in his murder"--